Long-term impact of COVID-19 pandemic on fear of COVID-19 and psychological distress among the general population in Japan: a longitudinal study - Hironori Yada; Ryo Odachi; Keiichiro Adachi (BMJ Open)
Objectives The long-term impact of the COVID-19 pandemic on the mental health issues of the general population in Japan is unclear. Thus, we examined the long-term effects of the COVID-19 pandemic on fear of COVID-19 and psychological distress and determined their causal relationships among the general population in Japan.Design and setting A longitudinal online survey was conducted by a Japanese online survey company to investigate the items regarding personal demographics, fear of COVID-19 (Japanese version of the fear of COVID-19 scale) and psychological distress (Japanese version of the Kessler 6 scale).Participants The participants were 274 individuals (women=44.2%) with a mean age of 51.6 years (SD=13.6) who responded to the online surveys in September 2020 (Time 1: T1) and January 2023 (Time 2: T2).Results The paired t-test showed that fear of COVID-19 decreased significantly from T1 to T2 (t=2.79, df=273, p<0.01, d=0.16). The χ2 test showed that the proportion of those at high risk for psychological distress remained the same (χ2=1.33, df=1, n.s.). Furthermore, in a two-panel cross-lagged analysis to determine the causal relationship between fear of COVID-19 and psychological distress, fear of COVID-19 at T1 significantly predicted psychological distress at T2 (β=0.26, p<0.001). Additional multiple regression analyses adjusted for covariates (age, sex, marital status, COVID-19 status, etc) showed that worsening household finances (β=0.11, p<0.05) and avoiding contact with others (β=0.20, p<0.01) were associated with fear of COVID-19 at T2.Conclusions During the long-lasting COVID-19 pandemic, fear of COVID-19 decreased, but psychological distress did not change. In addition, fear of COVID-19 predicted psychological distress and was associated with poorer household finances and avoiding contact with others. Mental health professionals and policymakers should continue to support mental health issues following the long-lasting COVID-19 pandemic through interventions focused on promoting financial support and social interactions to reduce fear of COVID-19.